2018
DOI: 10.1152/ajpheart.00290.2018
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin triggers splenic contraction and irreversible dysregulation of COX and LOX that alters the inflammation-resolution program in the myocardium

Abstract: Doxorubicin (DOX) is a widely used drug for cancer treatment as a chemotherapeutic agent. However, the cellular and integrative mechanism of DOX-induced immunometabolism is unclear. Two-month-old male C57BL/6J mice were divided into high- and low-dose DOX-treated groups with a maintained saline control group. The first group was injected with a high dose of DOX (H-DOX; 15 mg·kg·wk), and the second group was injected with 7.5 mg·kg·wk as a latent low dose of DOX (LL-DOX). H-DOX treatment led to complete mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 40 publications
2
31
0
Order By: Relevance
“…Furthermore, through transcription factor modulation, ANT increase NLRP3 expression, thus stimulating the release of the proinflammatory interleukins (IL)-1β and IL-6 [ 21 ]. Additionally, ANT-dependent inhibition of cyclooxygenase and lipoxygenases reduces cardiac availability of anti-inflammatory mediators (such as prostacyclins), promoting cardiac damage [ 22 , 23 ].…”
Section: Oxidative Stress and Inflammation As Possible Contributors To Cardiac Damagementioning
confidence: 99%
“…Furthermore, through transcription factor modulation, ANT increase NLRP3 expression, thus stimulating the release of the proinflammatory interleukins (IL)-1β and IL-6 [ 21 ]. Additionally, ANT-dependent inhibition of cyclooxygenase and lipoxygenases reduces cardiac availability of anti-inflammatory mediators (such as prostacyclins), promoting cardiac damage [ 22 , 23 ].…”
Section: Oxidative Stress and Inflammation As Possible Contributors To Cardiac Damagementioning
confidence: 99%
“…aspirin), the magnitude of infarction (minor, major, or massive), or ageing. We did not have data on diet or over‐the‐counter medications and recognize that these factors need to be considered in interpreting levels of lipid mediators in plasma of the individual patient . The influence of SES on CV disease is widely recognized.…”
Section: Discussionmentioning
confidence: 99%
“…We did not have data on diet or over-the-counter medications and recognize that these factors need to be considered in interpreting levels of lipid mediators in plasma of the individual patient. 37,[46][47][48] The influence of SES on CV disease is widely recognized. Although we collected information on education, income, and health insurance, we could not stratify by SES due to the small sample size.…”
Section: Study Limitationsmentioning
confidence: 99%
“…17 It is known that the M1/M2 macrophage polarization balance regulates the fate of an organ in inflammation or injury. 18 Jadapalli et al 19 reported that the LL-DOX caused myocardial apoptosis and cardiac dysfunction. It has also been shown that DOX triggers splenic contraction and irreversible dysregulation of cyclooxygenase (COX) and lipoxygenase (LOX), which alter the inflammation-resolution program in the myocardium with decreasing CD169 + metallophilic macrophages.…”
Section: Discussionmentioning
confidence: 99%